2016
DOI: 10.1039/c5ra24013a
|View full text |Cite
|
Sign up to set email alerts
|

Efficient conversion of glucose to 5-hydroxymethylfurfural using bifunctional partially hydroxylated AlF3

Abstract: Mesoporous AlF3 material bearing both Lewis and Brønsted acid sites exhibits high catalytic performance in glucose-to-fructose isomerization and subsequent dehydration to HMF (57.3% yield).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Therefore HMF selectivity and yield were reduced. This is in agreement with the other manuscrips that were published in this field [21,[58][59][60][61] . In Fig.…”
Section: The Influence Of Reaction Time On Dehydration Reaction Of Frsupporting
confidence: 93%
“…Therefore HMF selectivity and yield were reduced. This is in agreement with the other manuscrips that were published in this field [21,[58][59][60][61] . In Fig.…”
Section: The Influence Of Reaction Time On Dehydration Reaction Of Frsupporting
confidence: 93%
“…Lignocellulosic biomass is considered to be the most abundant resource on the earth, which has been extensively explored as a renewable feedstock for the production of value‐added chemicals and biofuels . Among various chemicals derived from biomass, 5‐hydroxymethylfurfural (HMF) is an important platform molecule, and has a wide range applications in the manufacture of plastics, surfactants, solvents, fuels, and pharmaceuticals …”
Section: Introductionmentioning
confidence: 99%
“…[4,5] Among variousc hemicals derived from biomass,5hydroxymethylfurfural (HMF) is an important platform molecule,a nd has aw ide range applications in the manufacture of plastics,s urfactants,s olvents,f uels,a nd pharmaceuticals. [6][7][8][9][10] In general, both homogeneous and heterogeneous catalysts can catalyze carbohydrates such as fructose,g lucose,a nd cellulose being transformed into HMF under relatively harsh conditions. [11][12][13][14] However, HMFi sq uite unstable in acidic media or even at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, Lu et al. reported that a high HMF yield of 57.3 % was achieved by using bifunctional partially hydroxylated AlF 3 , which possesses both Lewis acid and Brønsted acid sites …”
Section: Introductionmentioning
confidence: 99%
“…[33] Surprisingly,L uet alr eported that ah igh HMF yield of 57.3 %w as achieved by using bifunctionalp artially hydroxylated AlF 3 ,w hich possesses both Lewis acid and Brønsted acid sites. [34] Sn-b zeoliteisa ne xcellent solid Lewis acid catalyst for the isomerizationo fg lucose into fructose. Romµn-Leshkov et al and Wolf et al reported that the isomerizationo fg lucose over Sn-b was catalyzed by the frameworkS ns ites through an intramolecular hydride shift reaction.…”
Section: Introductionmentioning
confidence: 99%